Inherent and multiple strain hardening imparting synergistic ultrahigh strength and ductility in a low stacking faulted heterogeneous high-entropy alloy. (15th January 2023) - An, Zibing; Mao, Shengcheng; Liu, Yinong; Yang, Luyan; Vayyala, Ashok; Wei, Xiao; Liu, Cheng; Shi, Caijuan; Jin, Huixin; Liu, Cuixiu; Zhang, Jianxin; Zhang, Ze; et al.
Abstract: Alloys with high yield strength and ductility are attractive for application because of their potential to offer mass reduction, energy savings, and enhanced structural reliability. However, increasing strength usually comes at the expense of ductility, which is commonly known as the strength-ductility trade-off for metal alloys. In this work, we explored a strategy of using a heterogeneous grain size structure and a reduced stacking fault energy in a CoCrFeNiMn FCC high entropy alloy to overcome the limitations of this trade-off. By this approach, the alloy achieved a yield strength of 980 MPa, a tensile strength of 1385 MPa, and tensile elongation to failure of 48% benefiting from cooperative strain hardening via multiple mechanisms, such as hetero-deformation induced (HDI) hardening, deformation twinning, Frank-Read dislocation sources and Lomer–Cottrell dislocation locks instigated by such structures. These micromechanisms of deformation help to harden the alloy via in situ refinement of the mean free paths for dislocations. Graphical abstract: Image, graphical abstract